Life Stories and the Colonial Period in West Africa - (:unkn) unknown (My University, 2020)
Here, one can find a reflection on the historical significance of three life stories. They were published through the joint authorship of their hero and of the author of this notice, who shaped them. They were collected from 1987 to 2003, among personalities who grew up in the years 1920: the Malians, Almamy Yattara and Bocar Cissé, and the Guinean al‑hadji Thierno Mouhammadou Baldé. Although these life stories also bring a lot of information about Africa before colonial rule and since independence, the present analysis will be limited to the colonial period. We shall first locate our three texts among similar life stories or novels published in West Africa. We will show their contribution to Colonial history, that is more often viewed from external lenses than seen here through the eyes of colonised peoples. This study provides an opportunity to reflect on the theoretical issues of such documents, and about the possible future for that sort of published work.
Keywords: African Research